A Method of Generating Engineering Test Sequence for Urban Rail Transit CBTC System Based on Formalization. Issue 1 (June 2020) - Si, Xinyue; Kuang, Wenzhen; Li, Qiang
Abstract: In recent years, with the rapid development of urban rail transit, Communication Based Train Control system is very important to improve the operation efficiency and ensure the traffic safety. Before urban rail transit lines are put into operation, they need to be tested strictly. In view of the lack of unified test standards, specifications and low test efficiency, a formal test sequence generation method for CBTC system is proposed. Firstly, the test line is divided into several test segments; secondly, analyze the constraint conditions of test cases and get the expression of constraint relationship of test cases; thirdly, analyze the characteristic quantity that can represent the line characteristics, and get the line characteristic expression; and then match test cases with test segments using matching algorithm; finally, concatenate test cases into test sequences using the concatenation algorithm. The results show that the test sequences generated by this method meets the test requirements of CBTC system. The test sequences cover all test cases. And the method can effectively improve the test efficiency.